Sustainable urban water and sanitation in India: review of a national programme - Kavita Wankhade; Geetika Anand (2014)
Since 2005, the Government of India has been financing a massive urban infrastructure programme called Jawaharlal Nehru National Urban Renewal Mission (JNNURM) with the objectives of ‘encouraging reforms’ and ‘fast tracking planned development of cities’. Targetted mainly at 65 cities, the JNNURM made available financing for urban infrastructure and governance improvements, and for extending shelter and basic services to the urban poor. A large proportion of the investments made by cities under the programme were in the water and sanitation sector. This paper examines the results and emerging issues related to the programme investments, and assesses whether and how these investments appear to have contributed to promoting sustainability in water and sanitation services in urban India.